Comparison of ultrasonographic assessment of synovitis and joint vascularity with radiographic evaluation in a randomized, placebo-controlled study of infliximab therapy in early rheumatoid arthritis. - Taylor, P; Steuer, A; Gruber, J; Cosgrove, DO; Blomley, M; Marsters, P; Wagner, C; McClinton, C; Maini, R (2004)
OBJECTIVE: To investigate sensitive ultrasonographic imaging methods for detection of synovial thickness and vascularity to discriminate between patients with early rheumatoid arthritis (RA) receiving infliximab + methotrexate (MTX) versus placebo + MTX over 18 weeks, and to compare the relationship between synovial thickening and vascularity at baseline and radiologic damage to joints of the hands and feet at 54 weeks. METHODS: Patients with early RA (duration <3 years) receiving stable dosages of MTX were randomly assigned to receive blinded infusions of 5 mg/kg infliximab (n = 12) or placebo (n = 12) at weeks 0, 2, 6, and then every 8 weeks until week 46. At baseline and week 18, clinical assessments were performed, and metacarpophalangeal joints were assessed by high-frequency ultrasonography and power Doppler ultrasonography measurements. Radiographs of the hands and feet taken at baseline and at 54 weeks were evaluated using the van der Heijde modification of the Sharp method (vdH-Sharp score). RESULTS: Using changes in the total vdH-Sharp score over 54 weeks and changes in synovial thickening and joint vascularity at 18 weeks, we were able to distinguish those patients receiving infusions of infliximab + MTX from those receiving placebo + MTX. Sonographic measurements of synovial thickening and vascularity at baseline in the placebo + MTX group demonstrated clear relationships with the magnitude of radiologic joint damage at week 54. Infliximab + MTX treatment abolished these relationships. CONCLUSION: The delay or reversal of inflammatory and joint-destructive mechanisms in patients with early RA was already apparent following 18 weeks of treatment with infliximab + MTX and was reflected in radiologic changes at 54 weeks.